(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Analytical dependences of Hall’s constant, Hall’s angle and Hall’s transverse potential difference on magnetic induction for diluted binary solutions of electrolytes are obtained. The nonlinear character of these dependences known from experimental data is confirmed. The extreme values of magnetic induction at which Hall’s transverse potential difference and Hall’s angle obtain their maximum values, are estimated and juxtaposed with experimental data for various ions. The extreme values of magnetic induction are optimal ones, since at these values Hall’s effect in the given solution is manifested stronger.